New Class of Hydrido Iron(II) Compounds with cis‐Reactive Sites: Combination of Iron and Diphosphinodithio Ligand. Issue 16 (28th July 2016) - Liu, Jianguo; Zhang, Fanjun; Zhang, Ailing; Tong, Qingxiao; Tung, Chen‐Ho; Wang, Wenguang
Abstract: The cationic complex [Fe(P2 S2 )(NCMe)2 ] 2+ (P2 S2 =(Ph2 PC6 H4 CH2 S)2 (C2 H4 ) ([1 (NCMe)2 ] 2+ )), with two MeCN ligands in a cis orientation, was synthesized and characterized. The MeCN ligand in [1 (NCMe)2 ] 2+ undergoes further substitution by a hydride ligand or CO to give iron(II) hydrides [H1 (NCMe)] +, [H1 H] 0, and [H1 (CO)] + . The order of reactivity of the hydrides was [H1 H] 0 >[H1 (NCMe)] + >[H1 (CO)] +, and was illustrated by their reactions toward protic acids, the organic cation of 10‐methylacridinium (MeAcr + ) as a hydride acceptor, and intermolecular hydride transfer reactions among these ferrous compounds. For example, MeAcr + was reduced initially by a one‐electron transfer process from [H1 H] 0, resulting in competing reactions of MeAcr . dimerization, hydrogen atom transfer from [H1 H] + to MeAcr ., and decomposition of [H1 H] + . MeAcrH was produced in excellent yields through a single‐step H − transfer from [H1 (NCMe)] + to MeAcr +, but [H1 (CO)] + was inactive toward MeAcr + . Abstract : Reactive combination : Hydrido iron(II) compounds [HFe(P2 S2 )X] n + (P2 S2 =(Ph2 PC6 H4 CH2 S)2 (C2 H4 ); X=MeCN, H, and CO), with H − and X ligands in a cis orientation were synthesized and characterized. The reactivity of the hydrides was illustrated by their reactions toward protic acids and the organic cation of 10‐methylacridinium (MeAcr + ) as a hydride acceptor (see scheme).